Pengaruh Influencer Marketing dan Harga terhadap Minat Pembelian Ulang pada Produk Skincare Glad2Glow di Kota Surakarta - Adelya Ardhana; Etika Indah; Nindia Mayerli; Velani Nur Kholifah; Rayhan Gunaningrat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The increasingly fierce competition in the skincare industry is driving companies to implement effective marketing strategies to increase consumer repurchase intention. This study aims to analyze the influence of influencer marketing and price on repurchase intention of Glad2Glow skincare products in Surakarta City. This study used a quantitative approach with a survey method of fifty respondents who had purchased and used Glad2Glow products. The sampling technique used purposive sampling, while data collection was conducted through questionnaires. Data were analyzed using multiple linear regression with the help of SPSS. The results of validity and reliability tests indicate that all statement items are valid and reliable and therefore suitable for use in the analysis. The results show that influencer marketing has a positive and significant effect on repurchase intention, indicating that credible influencers who are in line with the product's character can build consumer trust and encourage repurchase. In addition, price also has a positive and significant effect on repurchase intention, with a more dominant effect than influencer marketing. Consumers consider the suitability between price, quality, and product benefits before making a repurchase. The results of the simultaneous test show that influencer marketing and price together have a significant effect on repurchase intention. This study concludes that the combination of the right influencer marketing strategy and pricing that is in line with consumer value perceptions plays an important role in increasing the interest in repurchasing Glad2Glow skincare products in Surakarta City.